Comparison of neonatal birthweights and fetomaternal outcomes in gestational diabetes-on diet, metformin and insulin - Dixit, Siddhi Shree; S., Sudha; C. R., Greeshma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Review suggested that neonatal birthweight in insulin group was higher than in metformin and diet and metformin had overall better fetomaternal outcomes. We wanted to understand the trend in the patients visiting our hospital. Methods: This is an observational comparative study conducted in Department of Obstetrics and Gynaecology, AIMS Kochi from 2019-2021. All antenatal patients were screened and total of 153 patients meeting inclusion and exclusion criteria were studied. The data was collected and analysed using SPSS 20 software. Results: The neonatal birthweight the three groups were comparable, with no significant difference (3.05±0.42 kgs in diet; 2.92±0.37 kgs in metformin; 3.11±0.41 kgs in insulin; p=0.092) and maternal pre-pregnancy weight was associated with birthweight. Insulin group had higher age (31.17±5.54 years versus 27.59±4.62 years in OHA and 29.43±4.56 years in diet; p<0.001). Insulin group delivered at an earlier gestation (37 weeks versus 38 weeks; p<0.001) and most common mode of delivery was cesearean section (74.6% in insulin; 54.2% in diet and 49.8% in OHA). NICU admission (45.8% versus 10.8% in diet and 15.4% in OHA; p<0.001) and need for phototherapy (1.5% in metformin versus 5.4% in diet and 11.8% in insulin; p=0.067) was lesser in metformin group. Conclusions: Strict glycemic control is important in preventing macrosomia Metformin overall has good fetomaternal outcomes compared to diet or insulin.